2015
DOI: 10.1002/pon.4014
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, medical, and psychosocial predictors of benefit finding among caregivers of childhood cancer survivors

Abstract: Objective There is a growing body of literature examining benefit finding, or finding positive outcomes in the face of adversity, among both adults and children with chronic conditions, and to some degree among caregivers. This study examined demographic, medical, and psychosocial predictors of greater benefit finding specifically among caregivers of childhood cancer survivors. Methods Caregivers of children who had completed treatment for cancer (n=83) completed measures assessing child and caregiver demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 46 publications
5
71
0
5
Order By: Relevance
“…Since FCs of pediatric cancer patients are subjected to a stressful and vulnerable situation due to the uncertainty and the fear of loosing their children, they are at high risk of developing psychological problems as compared with other groups . In this scenario, religious struggles may appear as a reaction to this situation and might seriously compromise mental health and well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since FCs of pediatric cancer patients are subjected to a stressful and vulnerable situation due to the uncertainty and the fear of loosing their children, they are at high risk of developing psychological problems as compared with other groups . In this scenario, religious struggles may appear as a reaction to this situation and might seriously compromise mental health and well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cancer remains a life‐changing diagnosis with substantial prognostic uncertainty and high caregiving demands; affecting both children/adolescents as well as their parents who usually provide extensive care . Studies have shown that these family caregivers (FCs) are subjected to physical and psychological burden during and after their children's medical care …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are likely additional variables that are important in predicting QoL that may interact with benefit finding, such as spiritual coping and illness impact. 56,57 These variables should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Spirituality for the pediatric cancer patient and family was defined through wellness, positivity, coping, distress adaptation, and life beliefs. 3,40,50,54,55 Spirituality definitions included transcendence of one's experience and growth in and through suffering. 39,41,56 The theme of spiritual hope was defined in the articles as "intentional hope" and "hope as inner strength."…”
Section: Definitions Of Spiritualitymentioning
confidence: 99%